Survival Rates of Anterior-Region Resin-Bonded Fixed Dental Prostheses: An Integrative Review - Mendes, José Manuel; Bentata, Anne Le Guen; de Sá, Juliana; Silva, António Sérgio (European Journal of Dentistry, 2021)
This study aimed to review clinical publications involving anterior-region resin-bonded fixed partial dentures to evaluate their survival rates vis-à-vis their materials and design. An electronic search was conducted using PubMed/MEDLINE to identify articles that reported on the longevity of anterior resin-bonded fixed dental prostheses published between 2000 and 2020. Only primary clinical studies that involved a follow-up after at least 3 years were included in this review. A statistical analysis was performed to evaluate resin-bonded fixed dental prostheses’ survival rates in relation to their materials and design. This review ultimately included 23 clinical publications, comprising prospective studies, retrospective studies, and randomized controlled trials. Its statistical analysis estimated the studied prostheses’ 5-year survival rate at 86.2% for metal-framed prostheses, 87.9% for zirconia prostheses, 93.3% for alumina prostheses, 100% for glass or ceramic prostheses, and 81.7% for fiber-reinforced composite restorations. Failure rates did not significantly differ between the different material groups or between the single- and double-retainer groups. Resin-bonded fixed dental prostheses present excellent 5-year clinical longevity in the anterior sector and a favorable benefit/risk/cost ratio. Currently, no consensus has been established on an ideal material for these restorations. Cantilever design tends to limit constraints on the prostheses’ retainers and, thus, increases their survival time. All-ceramic cantilever fixed partial dentures can be considered as a definitive therapy, given their high success and survival rates. They are an optimal solution for adolescents or young adults facing potentially continuous growth.
Keywords: bridge; cantilever; fixed dental prostheses; resin-bonded; survival rate